Health Belief Model on the Determinants of Human Papilloma Virus Vaccination in Women of Reproductive Age in Surakarta, Central Java - Yulia Fitriani; Ambar Mudigdo; Rita Benya Andriani (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Cervical cancer is a type of cancer that develops in a woman's cervix. Cervical cancer is caused by a human papillomavirus (HPV). Cervical cancer ranked fourth against most women's cancer. The incidence of cervical cancer was estimated at 528,000 (7.9%) cases worldwide causing 266,000 deaths in 2012. The HPV vaccine can protect women from HPV infection, thus lowering the risk of cervical cancer. This study aimed to analyze the determinants of HPV vaccination in women of reproductive age in Permata Harapan Oncology Clinic, Surakarta, Central Java, using Health Belief Model.Subjects and Method: This was an analytic observational study with a case-control design. This study was conducted at Permata Harapan Oncology Clinic, Surakarta, from January to February 2018. A total study of 200 study subjects was selected by fixed disease sampling. The dependent variable was HPV vaccination. The independent variables were knowledge, perceived seriousness, perceived susceptibility, perceived barrier, perceived benefit, family income, and family support. The data were collected by questionnaire and analyzed by a multiple logistic regression.Results: HPV vaccination increased with better knowledge (OR=7.97; 95% CI= 1.50 to 42.38; p= 0.015), perceived seriousness (OR=22.81; 95% CI= 6.06 to 85.86; p<0.001), perceived susceptibility (OR=4.03; 95% CI= 1.25 to 13.09; p=0.020), , perceived benefit (OR=6.57; 95% CI= 1.88 to 22.98; p=0.003), family income (OR=5.32; 95% CI= 1.57 to 18.07; p=0.007), and family support (OR=6.86; 95% CI= 1.55 to 30.36; p= 0.011). HPV vaccination decreased with perceived barrier (OR=0.14; 95% CI= 0.04 to 0.51; p=0.003).Conclusion: HPV vaccination increases with better knowledge perceived seriousness, perceived susceptibility, perceived benefit, family income, and family support, but decreases with perceived barrier.Keywords: HPV vaccination, knowledge, perceived seriousness, perceived susceptibility, perceived barrier, perceived benefit, family income, family supportCorrespondence: Yulia Fitriani. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: yuliafitriani38@gmail.com. Mobile: 085655708946.Journal of Health Promotion and Behavior (2018), 3(1): 16-26https://doi.org/10.26911/thejhpb.2018.03.01.02